PERFORMANCE STUDY OF FLUIDIZED BED BAGASSE DRYER WITH NOVAL ATTACHMENT OF DISTRIBUTORS AND ORIFICES - V. SRINIVASAN, V.SUBRAMINIAN , M SATHESH BABU , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Sugar cane bagasse can be used as fuel in boilers to produce steam and electricity in co-generation power plant. After many stages of milling process of sugar cane, the byproduct named as bagasse is available in different ranges of size of particles called as pith with higher percentage moisture content. The size of the bagasse particles varies from 2mm to 6mm after the depithing process, and this would be used as fuel in the co-generation power plant boilers of sugar cane processing industries. Due to high ranges of moisture content from 48% to 55%, the pith needs more than the normal percentage of excess amount of oxygen for complete combustion in the boiler. Few percentages of heat energy produced and have to be utilized by the wet bagasse to vaporize the surface moisture as well as the inner moisture content by the diffusion process. The loss of heat energy utilized to evaporate the moisture content reduces the boiler efficiency. Two hot air flow distributors of different shape placed in the fluidized bed dryer increased the rate of evaporation of moisture content by uniformly distributed hot air. On the surface of the two distributors were perfectly drilled and welded by two rows of orifices with certain included angle for the hot air flow. The hot air flow from the orifices makes countercurrent flow effect against the bagasse feeding from the hopper from the top of the fluidized bed dryer. Thus, the countercurrent flow effect makes a better mixing of solid – gaseous particles where the removal of moisture content of the bagasse. A slow speed rotating stirrer with bevel gear attachment and chain and sprocket driven mechanism into the fluidized bed dryer called mechanical agitator to agitate by spreading the bagasse across the surface area covered on the perforated plate to improve the evaporation rate of the moisture. The performance of the fluidization behavior of the dryer had been evaluated interms of moisture content reduction. The effect of temperature and the high velocity jet of hot air flow for the given time also considered for evaluating the performance of the fluidized bed dryer.